Colloquial German the complete course for beginners - Hatherall, Dietlinde; Hatherall, Glyn; Routledge (Firm) (Boca Raton, FL: Routledge, 2009)
Colloquial Germanis easy to use and completely up-to-date. Specially written by an experienced teacher for self-study or class use, the course offers you a step-by-step approach to written and spoken German
Title from container
Keywords: German language; German language -- Study and teaching; German language -- Grammar